Digital communications principles and systems - Otung, Ifiok (IET telecommunications series, 2014)
The book has 12 chapters, these are discussed about overview of digital communication, linear channels and systems, nonlinear systems, baseband signal sampling and passband signal sampling, quantisation and PCM, source coding and lossless data compression, line codes, bandlimited AWGN channel, digital signal transmission, noise impact, error control coding, digital transmission link analysis and design.